Legal Positivism Influence on Law Enforcement and Judicial Practice in Indonesia - Kamil, Renita (JUSTISI, 2025)
The study aims to examine the influence of legal positivism on law enforcement and judicial practices in Indonesia, particularly in the context of its limitations in realizing substantive justice. The main focus is on the issues of customary land rights, human rights enforcement, and corruption eradication. This method is a normative qualitative approach combining doctrinal analysis and comparative law. Data was collected through a literature study of relevant laws and regulations, court decisions, and academic literature. This method is used to explore and interpret the principles of legal positivism and its influence on the Indonesian legal system, without involving empirical data collection. The novelty of this study lies in its interdisciplinary approach that integrates classical legal positivism theory with contemporary challenges faced by Indonesia's pluralistic legal system. The research introduces the concept of “inclusivity positivism” which suggests that the legal system can retain a formal normative structure, yet still be accommodating to principles of substantive justice, constitutional values, and international human rights norms. The results show that the rigid application of legal positivism often hinders the achievement of social justice. In cases such as customary land rights and corruption eradication, courts tend to prioritize written regulations even when they contradict social realities and constitutional values. The findings also show that although the Constitutional Court has tried to balance with constitutional principles, implementation at the general court level is still limited due to the highly formalist legal culture. This study concludes that legal reform is needed that balances legal certainty and substantive justice. This can be achieved through updating laws in line with human rights principles, training judges in progressive constitutional approaches, and increasing the role of oversight institutions such as Komnas HAM. Thus, legal positivism in Indonesia does not need to be abandoned, but needs to be developed to be more responsive to the demands of justice in a pluralistic society.